2010
DOI: 10.1039/c0cc01254h
|View full text |Cite
|
Sign up to set email alerts
|

Excursions in polynuclear platinum DNA binding

Abstract: Polynuclear platinum agents are a structurally unique class of anti-cancer drugs, distinct from the cisplatin family. To describe the chemistry and biology of this class, it was necessary to challenge the accepted paradigms for the structure–activity relationships; design new chemotypes and delineate the structures and consequences of their DNA binding modes. This article summarizes the structural changes induced in DNA by both covalent (bond-forming) and non-covalent (ligand recognition) adducts. Solution (Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 91 publications
(198 reference statements)
3
97
0
2
Order By: Relevance
“…The dinuclear berenilplatinum complexes with amine ligands are cationic in nature and show excellent solubility in water. The adducts formed by these dinuclear platinum complexes are vastly different from the adducts formed by cisplatin 29 . It has been suggested that the distortions induced by these complexes are only weakly recognized by DNA repair proteins.…”
Section: Discussionmentioning
confidence: 98%
“…The dinuclear berenilplatinum complexes with amine ligands are cationic in nature and show excellent solubility in water. The adducts formed by these dinuclear platinum complexes are vastly different from the adducts formed by cisplatin 29 . It has been suggested that the distortions induced by these complexes are only weakly recognized by DNA repair proteins.…”
Section: Discussionmentioning
confidence: 98%
“…36 41 Este complexo liga-se no sulco maior, podendo formar ligações cruzadas flexíveis, intra e interfitas de longo alcance, sendo esta última, a principal delas. 37 Por causa disso, a interação deste complexo causa leves distorções na molécula do DNA, que fazem com que estes adutos não sejam reconhecidos pelas proteínas HMG do sistema biológico.…”
Section: Complexos Polinucleares De Platina(ii)unclassified
“…[Bis-{trans-diammineplatinum(II)}{μ-N,N′-(ethane-1,2-diyl)bis-(2-methylisonicotinamide)}] chloride dihydrate, complex (10) …”
Section: Synthesis Of Protected Platinum Complexesmentioning
confidence: 99%
“…1), which displayed excellent activity in cisplatin sensitive and resistant cancers in both in vitro and in vivo models. 10,17,18 Whilst cisplatin forms short range, rigid, intrastrand cross-links, BBR3464 forms flexible, long and short range, inter-and intrastrand cross-links upon binding, 19 as well as inducing B-to Z-and B-to A-type DNA conformational changes. 18,20 Preclinical trials revealed cytotoxicity at concentrations one thousand times lower than the concentration required by cisplatin; 18 however, in human Phase I trials, systemic toxicity was found to be so severe that the maximum tolerated dose was just 0.9-1.1 mg m −2 , compared to cisplatin with an administrable dose of 20-120 mg m −2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation